2020
DOI: 10.1177/1748895819898513
|View full text |Cite
|
Sign up to set email alerts
|

‘Listen to me, his behaviour is erratic and I’m really worried for our safety . . .’: Help-seeking in the context of coercive control

Abstract: This article explores 12 female victim-survivors’ experiences of seeking protection from criminal justice agencies in Dyfed-Powys, an area in Wales. The discussion draws on rich qualitative data, from a series of narrative interviews held in 2015, which offers new insights into how coercive and controlling behaviours influence ‘help-seeking’. The findings suggest that for 12 women, deemed to be high-risk, the experience of actively engaging with criminal justice agencies, served to instil in them a sense that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Women remain at high risk of lethal and nonlethal violence from abusive ex-partners ( Brownridge, 2006 ), with one Canadian study reporting that separated and divorced women experience nine and four times, respectively, the prevalence of violence from their ex-partners than do married women ( Brownridge et al, 2008 ). There are limited UK-based studies on the prevalence of post-separation abuse, though in one UK study 90% of women reported experiencing post-separation abuse ( Sharp-Jeffs et al, 2018 ), and in a study based in Wales, looking at experiences of help-seeking at the juncture of leaving an abusive relationship, 10 out of 12 women reported experiencing post-separation abuse ( Wydall & Zerk, 2020 ). Furthermore, 18% of UK femicide cases included in the 2020 Femicide Report, that were by an intimate partner, occurred post-separation.…”
Section: Post-separation Abuse and Controlmentioning
confidence: 99%
“…Women remain at high risk of lethal and nonlethal violence from abusive ex-partners ( Brownridge, 2006 ), with one Canadian study reporting that separated and divorced women experience nine and four times, respectively, the prevalence of violence from their ex-partners than do married women ( Brownridge et al, 2008 ). There are limited UK-based studies on the prevalence of post-separation abuse, though in one UK study 90% of women reported experiencing post-separation abuse ( Sharp-Jeffs et al, 2018 ), and in a study based in Wales, looking at experiences of help-seeking at the juncture of leaving an abusive relationship, 10 out of 12 women reported experiencing post-separation abuse ( Wydall & Zerk, 2020 ). Furthermore, 18% of UK femicide cases included in the 2020 Femicide Report, that were by an intimate partner, occurred post-separation.…”
Section: Post-separation Abuse and Controlmentioning
confidence: 99%